Drivers of global carbon emission changes: A heterogeneity perspective of decomposition and attribution analysis - Liu, Xiao; Zhang, Yancai; Wang, Qunwei (Frontiers in Environmental Science, 2022)
Due to the differences in economic development, resource endowment, and historical accumulation, different types of countries have significant technical heterogeneity in carbon emissions. Identifying the driving factors of carbon emission changes, under the premise of distinguishing national heterogeneity, can provide a basis for the formulation of the “Differentiated Responsibilities” emission reduction policies. Therefore, this study introduces the idea of Meta-frontier into the traditional production-theoretical decomposition analysis, and constructs a new influencing factor analysis framework. Based on the newly built method, the empirical study of 60 representative countries draws the following three meaningful conclusions: (1) Different types of countries have obvious heterogeneity in technology, efficiency and change trend of energy use. Specifically, countries with higher energy intensity values generally have a quicker decline rate than those with lower energy intensity values. There exists “catch-up” effects for the backward to the advanced countries. (2) Decomposition results show that potential energy intensity (PEI) is the dominant factor reducing carbon emissions, especially for those large economic output with large energy consumption (Group-L) countries (0.604). Economic activity effect (ECA) is the most significant driving force for countries with small economic output and small energy consumption (Group-S), reaching 1.806. Meanwhile, the attribution results showed different characteristics in different groups of countries. The impact of various factors that reflect the heterogeneity of production process on carbon emissions mainly comes from the contribution of Group-L. (3) We suggest that, in the process of carbon reduction, large energy consumption countries should pay more attention to the gap between the development and speed of the world's cutting-edge technologies.